Extremal elements in a hypercomplex space - Stefanchuk, M. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
Extremal elements and a h-hull of sets in the n-dimensional hypercomplex space Hn are investigated. The class of H-quasiconvex sets including strongly hypercomplex convex sets and being closed with respect to intersections is introduced.